RESEARCHES ON QUALITATIVE AND QUANTITATIVE ANALYSIS, ON DURATION OF STORAGE IN VARIOUS VARIETIES OF APPLES - Mariana BURCEA; Mihai GIDEA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The research was made in an organic farm, located on a preluvosol soil type with pedoclimatic conditions that support the apple plantations in this area. In this paper, the aim was to establish the capacity to store the fresh fruit quality and to highlight the diseases of the storehouse, of the varieties existing in the grown variety. Six varieties of homologated varieties of apple (Florina, Generos, Golden Delicious, Idared, Jonathan and Redix) were taken into consideration in order to establish the ability to store the apple quality in fresh state. It was found that the lowest total loss, with values below 10%, was registered at V3-Idared (7.45%). This variant presented both low weight losses and depreciation due to disease attack. The same variety also retained its initial firmness with an insignificant difference during storage. At the same time, it was noted that the highest content of initial juice extracted, belongs to V3-Idared and V4-Florina variants with more than 600 ml/kg.